A community-based study to assess the prevalence and predictors of stunting among under-five children in Sheger City, Oromia, Ethiopia - Firomsa Botorie; Bilisom Balcha Abera; Abera Botorie; Abera Botorie; Asonya Abera; Abebe Dukessa Dubiwak; Abebe Dukessa Dubiwak; Tesfaye Getachew Charkos; Godana Arero Dassie (Frontiers in Nutrition)
BackgroundStunting is a serious public health issue in Ethiopia. However, due to the scarcity of studies, little is known about the prevalence and predictors of stunting among children under the age of five in urban areas, especially those close to the capital city of the country (Addis Ababa). Thus, the aim of this study was to assess the prevalence of stunting and its predictors among children under the age of five in Lega Tafo Lega Dadi, Sheger City, Oromia, Ethiopia.MethodsA community-based cross-sectional study was conducted on 566 children under the age of five using a systematic random sampling technique. Data were collected through face-to-face interviews, structured questionnaires, and anthropometric measurements. Afterward, the data were entered into EpiData (version 4.7) and exported to SPSS 26 for analysis. Anthropometric indices were calculated using WHO Anthro software (version 3.2.2). Bivariate and multivariable logistic regression analyses were performed to identify candidate variables and associated factors, respectively. An adjusted odds ratio (AOR) and its 95% confidence interval (CI) were used to assess the strength and significance of the association. A p-value of <0.05 was considered statistically significant. The goodness-of-fit for the model was assessed using the Hosmer-Lemeshow test.ResultsThe prevalence of stunting was 18.9% (95% CI: 16, 22%) among under-five children in our study setting. Children whose mothers were daily laborers (AOR: 10.3), whose mothers’ education level was primary school (AOR: 4.3), whose fathers were daily laborers (AOR: 4), who were born into families with an average birth interval of ≤24 months (AOR: 7.9), who were from families with a size ≥5 (AOR: 7.3), who had a history of diarrhea (AOR: 6.3), who had meals ≤3 times per day (AOR: 13.9), who were underweight (AOR: 2.8), who were breastfed for less than 2 years (AOR: 5.6), who had low dietary diversity (AOR: 6.3), and who experienced food insecurity (AOR: 3.6) were identified as the predictors of stunting in under-five children.ConclusionApproximately one-fifth of the under-five children were stunted in the study setting. Family occupational and educational status, average birth interval, family size, a history of diarrhea, meal frequency per day, underweight status, duration of breastfeeding, inadequate dietary diversity, and household food insecurity were all associated with stunting among the under-five children in the study setting.